The Human Right to Health Solidarity in the Era of Healthcare Commercialization - Arenas Catalán, Eduardo (Elgar Studies in Health and the Law, 2021)
This timely book offers a fresh perspective on how to effectively address the issue of unequal access to healthcare. It analyses the human right to health from the underexplored legal principle of solidarity, proposing a non-commercial understanding of the positive obligations inherent in the right to health.